Implementasi Model Pembelajaran E-Learning Berbasis Edmodo Dalam Meningkatkan Kemandirian Belajar Matematika Siswa - Chairawati Chairawati; Marzianis Marzianis (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2021)
English: The aim of this research is to increase students learning independence in learning mathematics using the Edmodo-based e-learning model. This research is a classroom action research which consists of 3 cycles. The subjects of this study were 29 students of class IX SMPN 10 Banda Aceh. The instrument of this research is an observation sheet on the implementation of learning with the Edmodo-based e-learning model, a questionnaire for students' learning independence. The results of the study indicate that learning mathematics with the Edmodo-based e-learning model can increase students' learning independence. After the implementation of learning with the Edmodo-based e-learning model, the learning independence of class IX students of SMPN 10 Banda Aceh has increased. This is indicated by an increase in the percentage of the average score of each indicator of students' learning independence in learning mathematics from cycle I to cycle II, and cycle III, namely: (a) students using learning strategies increased from 59.57% to 72.34%, and increased to 82.97% in the last cycle (b) students' motivation to learn increased from 63.15% to 78.94%, and in the third cycle increased to 90.52%, (c) students did planning increased from 61.11% to 77.77% , and finally became 94.44%. In general, the learning independence of class IX students of SMPN 10 Banda Aceh increased from an average of 61.27% to 76.35% and in the third cycle to 89.31% after the implementation of mathematics learning with the Edmodo-based e-learning model. The results of the final evaluation of students' abilities after learning with the e-learning model with Edmodo media also showed that 80% of students had reached the predetermined KKM value. Bahasa: Penelitian ini bertujuan untuk meningkatkan kemandirian belajar peserta didik dalam pembelajaran matematika menggunakan model pembelajaran e-learning berbasis edmodo. Penelitian ini merupakan penelitian tindakan kelas yang terdiri dari 3 siklus. Subjek penelitian ini adalah 29 peserta didik kelas IX SMPN 10 Banda Aceh. Instrumen penelitian ini adalah lembar observasi keterlaksanaan pembelajaran dengan model e-learning berbasis edmodo, angket kemandirian belajar peserta didik. Hasil penelitian menunjukkan bahwa pembelajaran matematika dengan model e-learning berbasis edmodo dapat meningkatkan kemandirian belajar peserta didik. Setelah dilaksanakan pembelajaran dengan model e-learning berbasis edmodo, kemandirian belajar peserta didik kelas IX SMPN 10 Banda Aceh mengalami peningkatan. Hal ini ditunjukkan dengan adanya peningkatan persentase skor rata-rata tiap indikator kemandirian belajar peserta didik dalam pembelajaran matematika dari siklus I ke siklus II, hingga sikulus III yaitu: (a) peserta didik menggunakan strategi belajar meningkat dari 59,57% menjadi 72.34%, dan meningkat menjadi 82.97% pada sikulus terakhir (b) peserta didik memiliki motivasi belajar meningkat dari 63.15% menjadi 78.94%, dan pada sikulus ke III meningkat menjadi 90.52 %, (c) peserta didik melakukan perencanaan meningkat dari 61.11% menjadi 77,77%, dan akhirnya menajdi 94.44%. Secara umum, kemandirian belajar peserta didik kelas IX SMPN 10 Banda Aceh meningkat dari rata-rata 61.27% menjadi 76.35% dan pada siklus III menjadi 89.31% setelah dilaksanakan pembelajaran matematika dengan model e-learnig berbasis edmodo. Hasil evaluasi akhir kemampuan peserta didik setelah pembelajaran dengan model e-learning dengan media edmodo juga menunjukkan 80 % peserta didik telah mencapai nilai KKM yang telah ditetapkan.